Consumo foliar da traça-das-crucíferas em couve e brócolis tratados com sinigrina - Bortoli, Sergio Antonio De; Carvalho, Jackeline Da Silva; Vacari, Alessandra Marieli; Goulart, Roberto Marchi (Instituto Biológico, 2014)
Leaf area estimation, based on their reduction due to consumption by phytophagous insects, is a basic methodology in several areas of Entomology, for instance, in studies about plant resistance, economic entomology and nutritional ecology. One of the factors that can affect the amount of leaf area consumed by insects is the presence of certain chemicals in the leaves, such as sinigrin in Brassicaceae. Thus, several concentrations of sinigrin were applied on the leaves of cabbage and broccoli (0.2, 0.4, 0.8, 1.6, and 3.2 mg/mL in 5% Tween20(r) solution) in order to measure leaf area consumption by larvae of P. xylostella, estimated by the percentage of area reduction, weight loss and visual scale of notes. The results show that the concentrations of 0.2, 0.4 and 3.2 mg/mL of sinigrin increase larvae consumption of P. xylostella on kale leaves and decrease it on broccoli leaves. The methodologies used provide similar results, and fresh weight measurements and visual grades are more practical.

A estimativa da área foliar, em função da sua redução causada pelo consumo por insetos filófagos, é uma metodologia básica em várias áreas da Entomologia, como, por exemplo, em estudos sobre resistência de plantas, entomologia econômica e ecologia nutricional. Um dos fatores que pode interferir na quantidade de área foliar consumida pelo fitófago é a presença de certos químicos nas folhas, como a sinigrina em brassicáceas. Dessa forma, foram aplicadas em folhas de couve e brócolis diversas concentrações de sinigrina (0,2, 0,4, 0,8, 1,6, e 3,2 mg/mL em solução a 5% de Tween20(r)), medindo-se o consumo da área foliar por lagartas de P. xylostella, o qual foi aferido pela porcentagem de redução da área, diferença de peso e escala visual de notas. Os resultados mostraram que as concentrações 0,2, 0,4 e 3,2 mg/mL de sinigrina aumentam o consumo em folhas de couve e diminuem em folhas de brócolis por lagartas de P. xylostella. As metodologias utilizadas proporcionam resultados similares, sendo as estimativas de peso fresco e nota visual mais práticas.
Leaf area consumed by diamondback moth feeding on kale and brocolis treated with sinigrin
Keywords: Plutella xylostella; glicosinolatos; Brassicaceae; crucíferas; Plutella xylostella; glucosinolates; Brassicaceae; cruciferous